2018
DOI: 10.1016/j.jval.2018.04.365
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Of Sacubitril/Valsartan In The Treatment Of Heart Failure In Costa Rica

Abstract: gained) over a 30-year time horizon. Sensitivity analyses were performed. ReSultS: Base-case results suggest that compared to ACEi, sacubitril/valsartan is associated with incremental costs of ₡3,385,614 and 0.53 QALYs gained, with an incremental cost-effectiveness ratio of ₡6,400,593 per QALY gained. Increased costs of pharmacological therapy were offset by reductions in hospitalization costs. All-cause-and CV-related mortality estimates were reduced at all time points. Expected survival estimates increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A study from Thailand concluded that sacubitril/valsartan may not be a cost-effective therapy in the base-case (ICER/QALY THB162,276; WTP THB160,000), and that risk of cardiovascular death in patients who received enalapril was the most influential model driver [36]. One-way SA indicated that the constant coefficient (Portugal [26], Singapore [40], Taiwan [31], Brazil [39], Costa Rica [38], and Colombia [41]) and agesquared coefficient (the Netherlands [43], Denmark [41]) in the Gompertz distribution of cardiovascular mortality were parameters that had the most influence on the CE results, but ICERs at the lower bound of the 95% CI remained below the WTP limits. In the CE models from Portugal (€36,059) [26], Denmark (Kr285,710) [41], Australia (A$71,404) [27], Sin- CV cardiovascular, ICER incremental cost-effectiveness ratio, TE treatment effect gapore (SG$1,447,103) [19], and Thailand (THB290,000) [36], the ICERs estimated at the upper bound of the 95% CI were above the country-specific thresholds.…”
Section: Parameters With the Highest Impact On Ce Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A study from Thailand concluded that sacubitril/valsartan may not be a cost-effective therapy in the base-case (ICER/QALY THB162,276; WTP THB160,000), and that risk of cardiovascular death in patients who received enalapril was the most influential model driver [36]. One-way SA indicated that the constant coefficient (Portugal [26], Singapore [40], Taiwan [31], Brazil [39], Costa Rica [38], and Colombia [41]) and agesquared coefficient (the Netherlands [43], Denmark [41]) in the Gompertz distribution of cardiovascular mortality were parameters that had the most influence on the CE results, but ICERs at the lower bound of the 95% CI remained below the WTP limits. In the CE models from Portugal (€36,059) [26], Denmark (Kr285,710) [41], Australia (A$71,404) [27], Sin- CV cardiovascular, ICER incremental cost-effectiveness ratio, TE treatment effect gapore (SG$1,447,103) [19], and Thailand (THB290,000) [36], the ICERs estimated at the upper bound of the 95% CI were above the country-specific thresholds.…”
Section: Parameters With the Highest Impact On Ce Resultsmentioning
confidence: 99%
“…CE models using a Markov structure with regression-based modeling generally considered hospitalizations, AEs, and health-related quality of life (HRQoL) within the “alive” health state. A model based on Markov structure using regression equations for outcomes was developed by McMurray et al for the UK [ 41 ] and was adapted for several countries, including Spain [ 37 ], Switzerland [ 25 ], Netherlands [ 43 ], Denmark [ 41 ], Sweden [ 28 ], Greece [ 47 ], Czech Republic [ 46 ], Portugal [ 26 ], Turkey [ 45 ], Singapore [ 40 ], Taiwan [ 31 ], South Korea [ 42 ], Brazil [ 39 ], Cost Rica [ 38 ], and Colombia [ 41 ]. A study from India by Gokhale et al adopted a cost-consequence analysis to predict HF hospitalizations and mortality with sacubitril/valsartan versus ACEi in patients with chronic HFrEF [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations